Enhancing Reading Ability Through the Cooperative Integrated Reading and Composition (CIRC) Model: A Study with Fifth-Grade Elementary School Students - Notanubun, Zainuddin; Ririhena, Ribka Lemy; Notanubun, Erwin (KnE Social Sciences, 2024)
Reading comprehension is a vital aspect of language proficiency that elementary school students must master. Proficient reading skills enable students to actively acquire diverse information efficiently. The cooperative integrated reading and composition (CIRC), is a teaching model designed to enhance students’ reading comprehension skills through collaborative learning activities. This research aims to investigate the impact of the CIRC model on the reading comprehension abilities of fifth-grade students at SD Negeri 1 Kairatu. Employing an experimental design with a one-group pretest and post-test setup, the study involved 41 students. The CIRC model served as an independent variable, while reading comprehension ability constituted the dependent variable. The research instrument utilized was a reading comprehension test. Data analysis was conducted via a paired sample t-test, revealing a significant difference in students’ reading comprehension abilities before and after learning with the CIRC model (p = 0.00, < 0.05). These findings underscore the effectiveness of the CIRC model in improving students’ reading proficiency. The study’s results underscore the importance of prioritizing reading skills development to enhance elementary students’ literacy levels. It recommends the widespread adoption and continuous practice of the CIRC model in elementary schools to cultivate students’ interest and competence in reading. This research contributes to the ongoing efforts to enhance reading education methodologies and promote literacy among elementary school students. Keywords: CIRC model, reading comprehension, reading literacy, elementary school students